Eksistensi Ibu Rumah Tangga Dalam Peningkatan Ekonomi Keluarga (Studi Kasus Program Mom Preaneurs Di Kota Samarinda) - Rifa'at Nur Rahmah; Moh Mahrus; Dedy Mainata (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
One of the forums that are developing skills and empowering housewives is the Mom Preaneurs program located in Samarinda City, East Kalimantan Province. To optimize the improvement of the family economy, these housewives will later be given skills training in financial management and entrepreneurship so that later they can open their own businesses so that these housewives can support and contribute to the family economy and are also able to improve their understanding and skills. - housewives to be more existent and productive. This type of research is a field research (Field Research) with a descriptive qualitative approach. Sources of data in this study using primary data sources and secondary data. In this study, the data collection technique was throughobservation, interviews with informants from the Head of Mom Prenuers, and ten members of Mom Prenuers, as well as documentation. With data analysis techniques, namely data reduction, data presentation, conclusion drawing and data validity. Based on the results of this study, it shows that the programs that are run in the management of Mom Prenuers are by providing training to housewives, Mentoring or mentoring after attending training, as well as Monitoring or monitoring the development of housewives who have been able to master the training. In improving the family economy, the efforts made by housewives after participating in the Mom Preneurs program are by establishing businesses such as cake making businesses, handicraft businesses, office stationery businesses (ATK), and convection businesses. This business really helps their family's economy.Keywords: Housewives, Family Economics, Mom Preaneurs Program